Teachers, race and student achievement in a randomized experiment - Dee, Thomas S. (NBER working paper series, 2001)
Recommendations for the aggressive recruitment of minority teachers are based on hypothesized role-model effects for minority students as well as evidence of racial biases among non-minority teachers. However, prior empirical studies have found little or no association between exposure to an own-race teacher and student achievement. This paper presents new evidence on this question by evaluating the test score data from Tennessee's Project STAR class-size experiment, which randomly matched students and teachers within participating schools. Empirical results based on these data confirm that the racial pairings of students and teachers in this experiment were independently given. Models of student achievement indicate that a one-year assignment to an own-race teacher significantly increased the math and reading achievement of both black and white students by roughly three to four percentile points.